Thermochemical isolation and characterization of nanofibrillated cellulose from Stipa obtusa fibers - Chavez, Bitia K. (2023)
This research aimed to establish a methodology for isolating and characterizing nanofibrillated cellulose (CNF) from Stipa obtusa, using low concentrations of reagents and their characterization. The fibers were collected in high Andean areas of Cusco in Peru, treated with the alkaline-assisted steam explosion, followed by bleaching and acid fibrillation procedures, and with steam explosion, using solutions with varying concentrations of oxalic acid. The CNF was characterized by analytical methods according to TAPPI standards and using XRD, FTIR, SEM, TEM, and TGA techniques. The optimum values for obtaining the CNFs were: alkaline treatment with NaOH 0.5 M and acid treatment with 8% (m/m) of oxalic acid. These parameters were used to obtain a CNF network with a non-uniform surface and diameters between 19 and 27 nm, 82.97% (m/m) of cellulose, and a crystallinity index of 52.92%. Furthermore, the results showed a progressive partial elimination of lignin and hemicellulose at each stage of isolation.